2009
DOI: 10.1038/npp.2009.77
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Brain Autoantibodies and Altered Excitatory Neurotransmitters in Obsessive–Compulsive Disorder

Abstract: Although serum autoantibodies directed against basal ganglia (BG) implicate autoimmunity in the pathogenesis of obsessive-compulsive disorder (OCD), it is unclear whether these antibodies can cross the blood-brain barrier to bind against BG or other components of the OCD circuit. It is also unclear how they might lead to hyperactivity in the OCD circuit. We examined this by investigating the presence of autoantibodies directed against the BG or thalamus in the serum as well as CSF of 23 OCD patients compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 29 publications
2
123
0
Order By: Relevance
“…Finally, antibodies (IgG) deposited in the striatum, thalamus, and frontal cortex of streptococcal-exposed rats, in line with evidence implicating the striatum in the pathogenesis of SC and PANDAS, and the striatum and frontal cortex in the pathophysiology of OCD. Thus, anti-striatal antibodies have been reported in serum and cerebrospinal fluid of SC (Bronze and Dale, 1993;Church et al, 2002;Husby et al, 1976), PANDAS (Gause et al, 2009;Pavone et al, 2004), and adult OCD patients (Bhattacharyya et al, 2009). In addition, functional imaging studies found hypermetabolism in the striatum of SC patients (Dilenge et al, 1999;Weindl et al, 1993) and in the striatum and frontal cortex of OCD patients (Huyser et al, 2009), which normalized after successful treatment (Dilenge et al, 1999;Huyser et al, 2009;Weindl et al, 1993), and imaging studies in PANDAS patients reported that the basal ganglia were enlarged (Giedd et al, 2000) and size correlated with anti-neural antibody titers (Giedd et al, 2000;Peterson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, antibodies (IgG) deposited in the striatum, thalamus, and frontal cortex of streptococcal-exposed rats, in line with evidence implicating the striatum in the pathogenesis of SC and PANDAS, and the striatum and frontal cortex in the pathophysiology of OCD. Thus, anti-striatal antibodies have been reported in serum and cerebrospinal fluid of SC (Bronze and Dale, 1993;Church et al, 2002;Husby et al, 1976), PANDAS (Gause et al, 2009;Pavone et al, 2004), and adult OCD patients (Bhattacharyya et al, 2009). In addition, functional imaging studies found hypermetabolism in the striatum of SC patients (Dilenge et al, 1999;Weindl et al, 1993) and in the striatum and frontal cortex of OCD patients (Huyser et al, 2009), which normalized after successful treatment (Dilenge et al, 1999;Huyser et al, 2009;Weindl et al, 1993), and imaging studies in PANDAS patients reported that the basal ganglia were enlarged (Giedd et al, 2000) and size correlated with anti-neural antibody titers (Giedd et al, 2000;Peterson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is the primary neurotransmitter within the CSTC and, while not currently conclusive, evidence suggests that disruptions in glutamate neurotransmission are apparent in patients with OCD [8][9][10]. Significantly higher levels of glutamate have been found in the cerebral spinal fluid and various regions of the brain, including the right caudate and orbitofrontal cortex of OCD patients [11][12][13]. High levels of glutamate are known to elicit oxidative stress [14], and increased oxidative stress has been detected in serum samples from those diagnosed with OCD [15][16][17], appearing to correlate with symptom severity [18].…”
Section: Introductionmentioning
confidence: 98%
“…To further investigate the role of ABGA in OCD, Bhattacharyya et al [35] examined ABGA in the serum and cerebrospinal fluid (CSF), and measured CSF amino acids (GABA, glutamate, glycine and taurine) in 23 drug-naïve adult OCD patients compared with 23 healthy controls. There was no significant difference in serum autoantibodies binding to basal ganglia homogenates (as assessed by Western blot), but there was more binding of CSF autoantibodies in OCD patients in contrast with controls, possibly indicating intrathecal ABGA synthesis.…”
Section: Abga: More Than a Biomarker?mentioning
confidence: 99%